2000
DOI: 10.1046/j.1365-4362.2000.00890.x
|View full text |Cite
|
Sign up to set email alerts
|

Pityriasis lichenoides‐like exanthem and primary infection by Epstein–Barr virus

Abstract: A 43‐year‐old man with a history of recurrent herpes simplex, and without a history of atopy, presented with a sudden appearance of an exanthem 10 days before presenting to the clinic. The exanthem affected the face, flexural areas, hands, and feet. No local symptomatology and no systemic involvement were observed. The exploration revealed a polymorphous exanthem formed by maculopapular lesions, umbilicated vesicles, crusts, and purpuric and necrotic elements, with a pattern of acute pityriasis lichenoides ( F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2001
2001
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 13 publications
0
6
0
1
Order By: Relevance
“…The rash disappeared within 7 days of the initiation of oral acyclovir treatment. 73 In 2003 Klein et al 74 reported a 23-yearold woman who presented with a 3-day history of fever, sore throat, jaundice, dark urine, and claycolored stools, as well as a cutaneous eruption clinically and histopathologically consistent with PLC. Results of laboratory studies indicated acute infectious mononucleosis, and as her serologic results for EBV, results of hepatic function tests, and constitutional symptoms improved, her cutaneous lesions resolved.…”
Section: Infectious Etiologymentioning
confidence: 99%
“…The rash disappeared within 7 days of the initiation of oral acyclovir treatment. 73 In 2003 Klein et al 74 reported a 23-yearold woman who presented with a 3-day history of fever, sore throat, jaundice, dark urine, and claycolored stools, as well as a cutaneous eruption clinically and histopathologically consistent with PLC. Results of laboratory studies indicated acute infectious mononucleosis, and as her serologic results for EBV, results of hepatic function tests, and constitutional symptoms improved, her cutaneous lesions resolved.…”
Section: Infectious Etiologymentioning
confidence: 99%
“…Evidence of serology, histopathology and treatment outcomes further suggested that the abnormal skin response of pityriais lichenoides could be a result of hypersensitivity reaction following the infection 2,3 . Among these, Toxoplasma gondii, 4 Epstein‐Barr virus, 5,6 parvovirus B19, M. pneumoniae, human immuno‐deficiency virus (HIV) 7 and group A β‐hemolytic streptococcus 8 have been indicated.…”
Section: Introductionmentioning
confidence: 99%
“…It is possible, however, that the exanthem occurring during EBV acute IM shows atypical features with a scarlatiniform, vesicular, or petechial pattern 3,4,10,11,21 . Indeed, our patient showed an atypically widespread erythematous‐papulovesicular eruption during the acute phase of IM, which is a very rare occurrence (Table 1).…”
Section: Discussionmentioning
confidence: 70%
“…We found 264 studies related to the possible cutaneous and mucosal manifestations during EBV acute infection; we selected the articles that more exhaustively reported the clinical and laboratory description of the case/cases, 5‐45 published from 1954 to 2018 (Table 1).…”
Section: Resultsmentioning
confidence: 99%